If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 16 + -3x Reorder the terms: 2(-2 + x) = 16 + -3x (-2 * 2 + x * 2) = 16 + -3x (-4 + 2x) = 16 + -3x Solving -4 + 2x = 16 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + 2x + 3x = 16 + -3x + 3x Combine like terms: 2x + 3x = 5x -4 + 5x = 16 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + 5x = 16 + 0 -4 + 5x = 16 Add '4' to each side of the equation. -4 + 4 + 5x = 16 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 16 + 4 5x = 16 + 4 Combine like terms: 16 + 4 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| -7x+y=-4 | | (2s+4)(2s-4)= | | 7x^2-5=2 | | x/4+10=34 | | 6x-2=-4x+7 | | -9=-20+a | | 17=2x-9 | | 4(x-2)+5x=10 | | 45/450 | | 31=3-4x | | 1+2x-3-4x-5=6 | | 3x/1=2x | | 5*10/4 | | 2(x+4)+5x=50 | | 5n+8=3n | | logs(4x-18)-logs(x-6)=1 | | 3.8=p/3-7.2 | | y/4=5+1 | | 6(x+3)=18 | | (4x-18)-logs(x-6)=1 | | ((x-2x)+2x(y+10xy))=0 | | (-31)(11)= | | 19x+(-4x+3)=2 | | 3*x-6=2*x+8 | | 4x/2+9 | | y+16/12=7/6-y-4/6 | | 0,5x+(-x+3)=19 | | 3x/2+3=2x/3+8 | | y+6/6=y+8/9 | | 48=3k-90 | | M/1=x+n/p | | 9/10x-9=0 |